Effect of Physical Activity versus Health Education on Physical Function, Grip Strength and Mobility - Santanasto, Adam J.; Glynn, Nancy W.; Lovato, Laura C.; Blair, Steven N.; Fielding, Roger A.; Gill, Thomas M.; Guralnik, Jack M.; Hsu, Fang‐Chi; King, Abby C.; Strotmeyer, Elsa S.; Manini, Todd M.; Marsh, Anthony P.; et al. (Journal of the American Geriatrics Society (JAGS), 2017)
Background Physical activity (PA) reduces the rate of mobility disability, compared with health education (HE), in at risk older adults. It is important to understand aspects of performance contributing to this benefit. Objective To evaluate intervention effects on tertiary physical performance outcomes. Design The Lifestyle Interventions and Independence for Elders (LIFE) was a multi‐centered, single‐blind randomized trial of older adults. Setting Eight field centers throughout the United States. Participants 1635 adults aged 78.9 ± 5.2 years, 67.2% women at risk for mobility disability (Short Physical Performance Battery [SPPB] <10). Interventions Moderate PA including walking, resistance and balance training compared with HE consisting of topics relevant to older adults. Outcomes Grip strength, SPPB score and its components (balance, 4 m gait speed, and chair‐stands), as well as 400 m walking speed. Results Total SPPB score was higher in PA versus HE across all follow‐up times (overall P = .04) as was the chair‐stand component (overall P < .001). No intervention effects were observed for balance (overall P = .12), 4 m gait speed (overall P = .78), or grip strength (overall P = .62). However, 400 m walking speed was faster in PA versus HE group (overall P =<.001). In separate models, 29% of the rate reduction of major mobility disability in the PA versus HE group was explained by change in SPPB score, while 39% was explained by change in the chair stand component. Conclusion Lower extremity performance (SPPB) was significantly higher in the PA compared with HE group. Changes in chair‐stand score explained a considerable portion of the effect of PA on the reduction of major mobility disability–consistent with the idea that preserving muscle strength/power may be important for the prevention of major mobility disability.